Pemberdayaan Kader Malaria Kampung Dalam Upaya Pemberantasan Malaria di Distrik Sentani Timur - Angki Irawan; Theresie Chindyana Herman; Yeyen Fien Natalia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
Malaria remains a public health problem in Indonesia, particularly Papua. Various efforts have been made to reduce cases, one of which is the formation of malaria control units in villages. The purpose of this non-commercial service is to improve your knowledge and skills in using health promotion media in the form of Papua Malaria Flipchart. Methods used strengthen village malaria cadres by expanding their knowledge on malaria, training them on the use of the Papua Malaria Flipchart health promotion media, and advising communities through village malaria cadres. That was it. The target group for community service is 12 village malaria cadres and her 3 malaria representatives. This activity was conducted in the East Sentani District, the working area of ​​the Harapan Health Center. Evaluation of this non-profit activity is pre- and post-testing of educational materials and community interviews in consultation with village malaria cadres. An indicator of the success of this activity was the increased knowledge and skills of village malaria cadres who used the Papua Emic Malaria Flipchart media to provide counseling. The results of this service show that the village malaria cadres improved their knowledge of malaria and their skills in using the Papua Malaria Flipchart during counseling. It was concluded that the results of the service increased the malaria knowledge and skills of malaria workers and the use of the Papua Malaria Flipchart.